Unveiling Heavy Metal Links: Correlating Dust and Topsoil Contamination in Vilnius Schools - Murat Huseyin Unsal; Gytautas Ignatavičius; Vaidotas Valskys (Land, 2024)
This study conducts a comprehensive analysis of the presence of heavy metals, specifically zinc (Zn), lead (Pb), copper (Cu), chromium (Cr), and arsenic (As), in dust samples collected from 24 schools in Vilnius during the year 2022. It compares these findings with topsoil data from prior investigations spanning from 2011 to 2023, obtained from the areas near the schools as well as multiple spots across Vilnius. The study reveals significant variations in the levels of heavy metals, providing a comprehensive understanding of the complex relationship between urban sources of pollution, environmental processes, and the correlation between soil and indoor dust pollution. An important aspect of this work is the application of principal component analysis (PCA) and hierarchical clustering on the datasets from 2017 and 2020, which unveiled separate clusters from both dust and soil samples. Three major clusters were identified, highlighting the dynamic character of heavy metal distribution in these environments. Pearson’s correlation analysis provided additional evidence, demonstrating significant relationships between specific heavy metals in both dust and soil samples, emphasizing the interlinked nature of these environments. Zinc (Zn) and Lead (Pb) were determined to be the most commonly found heavy metals in the dust samples, which could potentially pose a health hazard in educational environments. This study distinguishes itself by examining indoor dust in educational facilities and topsoil in Vilnius, providing crucial insights into the relationship between these two environmental matrices. Recognizing the geographical limitations of this study, further research could be expanded to other cities to validate and compare these findings.